2019
DOI: 10.1088/1755-1315/334/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameter Contributing to Lodging Resistance of F2 Population in Red Rice

Abstract: The effectiveness and successful of selection depend on the value of genetic variability, heritability and genetic advance estimation. The purpose of this research is to measure the value of genetic parameters (variability, heritability and genetic advance) of F2 lines derived from crossing of mutant red rice, local accession of red rice, and commercial upland rice varieties. This research used single plant design. The rice materials used in this research was the F2 seeds derived from hibridization between MR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Rice plant that are tolerant to Fe's stress have the ability to survive high fe concentration conditions. According to Mahender et al (2019) membrane so that it does not absorb Fe 2+ . According to (Noor & Khairuddin, 2013) Tolerant plants can also store Fe 2+ absorbed in old root, stem, or leaf tissues as a form of avoidance of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Rice plant that are tolerant to Fe's stress have the ability to survive high fe concentration conditions. According to Mahender et al (2019) membrane so that it does not absorb Fe 2+ . According to (Noor & Khairuddin, 2013) Tolerant plants can also store Fe 2+ absorbed in old root, stem, or leaf tissues as a form of avoidance of stress.…”
Section: Discussionmentioning
confidence: 99%
“…The value of variability and the estimated heritability are essential components that must be measured before determining the method and time for selection (Mustikarini et al 2019). The coefficient of genotypic variation (GCV) and the coefficient of phenotypic variation (PCV) are very useful in determining the amount of diversity that exists in the population and are the basis for variability criteria (Mustikarini et al 2019;Saidon et al 2020).…”
Section: Genetic Variability and Heritability Of Agronomic Traitsmentioning
confidence: 99%
“…The value of variability and the estimated heritability are essential components that must be measured before determining the method and time for selection (Mustikarini et al 2019). The coefficient of genotypic variation (GCV) and the coefficient of phenotypic variation (PCV) are very useful in determining the amount of diversity that exists in the population and are the basis for variability criteria (Mustikarini et al 2019;Saidon et al 2020). All traits showed high PCV than GCV, similar to the results reported by Srivastava et al (2017); Tiruneh et al (2021), indicating that the variance observed for the traits was more influenced by the genetic factors and suitable environment support the expression of genetic (Kartahadimaja et al 2021).…”
Section: Genetic Variability and Heritability Of Agronomic Traitsmentioning
confidence: 99%
“…The phenotypic variances were very far from each other shows the high influence of environment on black pepper traits (Preethy et al 2018). The value of variability is the important component to measure before determining the method and time to perform further selection (Mustikarini et al 2019). Characters that have a wide and quite wide phenotypic diversity can be utilized for developing superior varieties of black pepper.…”
Section: Agro-morphological Characters Of Black Pepper In Bangka Islandmentioning
confidence: 99%